Sie sind auf Seite 1von 4

ON SMARANDACHE TRIPLE FACTORIAL FUNCTION

You Qiying
College of Science, Changan University, Xian, Shaanxi, P.R.China

Abstract

For any positive integer n, the Smarandache triple factorial function d3f (n) is dened to be the smallest integer such that d3f (n)!!! is a multiple of n. In this paper, we study the hybrid mean value of the Smarandache triple factorial function and the Mangoldt function, and give a sharp asymptotic formula. Triple factorial numbers; Hybrid mean value; Asymptotic formula.

Keywords:

1. Introduction
According to [1], for any positive integer n, the Smarandache triple factorial function d3f (n) is dened to be the smallest integer such that d3f (n)!!! is a multiple of n. About this problem, we know very little. The problem is interesting because it can help us to calculate the Smarandache function. In this paper, we study the hybrid mean value of the Smarandache triple factorial function and the Mangoldt function, and give a sharp asymptotic formula. That is, we shall prove the following theorems. Theorem 1. If x 2, then for any positive integer k we have 1 (n)d3f (n) = x2
nx

1 k1 am + 2 m=1 logm x

+O

x2 , logk x

where 1 (n) = log p, 0, if n is a prime p ; otherwise,

and am (m = 1, 2, , k 1) are computable constants. Theorem 2. If x 2, then for any positive integer k we have (n)d3f (n) = x
nx 2

1 k1 am + 2 m=1 logm x

+O

x2 , logk x

where (n) is the Mangoldt function.

90

SCIENTIA MAGNA VOL.1, NO.1

2. One lemma
To complete the proofs of the theorems, we need the following lemma. Lemma. For any positive integer , if p (3 2) we have d3f (p ) = (3 2)p.

Proof. Since [(3 2)p]!!! = (3 2)p (3 3)p p, so p | [(3 2)p]!!!. On the other hand, if p (3 2), then (3 2)p is the smallest integer such that [(3 2)p]!!! is a multiple of p . Therefore d3f (p ) = (3 2)p.

3. Proof of the theorems


In this section, we complete the proofs of the theorems. Let a(n) = 1, 0, if n is prime; otherwise.

then for any positive integer k we have a(n) = (x) =


nx k 1 m! x 1+ log x logm x m=1

+O

x log
k+1

By Abels identity we have 1 (n)d3f (n)


nx

=
px

p log p =
nx

a(n)n log n
x 2

= (x) x log x = x
2 k 1

(t) (log t + 1) dt +O x2 logk x

1+
x 2

m! m log x m=1

k 1 t m! t k1 m! t+ +t + log t logm t log t m=1 logm t m=1

+O = x2

t (log t + 1) logk+1 t 1 k1 am + 2 m=1 logm x

dt +O x2 , logk x

On Smarandache triple factorial function

91

where am (m = 1, 2, , k 1) are computable constants. Therefore p log p = x2


px

1 k1 am + 2 m=1 logm x

+O

x2 . logk x

So we have 1 (n)d3f (n) = x2


nx

1 k1 am + 2 m=1 logm x

+O

x2 . logk x

This proves Theorem 1. It is obvious that d3f (p ) (3 2)p. From Lemma 1 we have (n)d3f (n)
nx

=
p x

log p [(3 2)p] +


p x p<(32)

log p [d3f (p ) (3 2)p] .

Note that (3 2)p log p


p x px

p log p p log p
p x

=
x log log p

p log p(2 1)
px1/

=
x px1/ 2 log log p

p log p(3 2) x2/ log x1/


x 2 log log p

x log3 x

and log p [df (p ) (3 2)p]


p x p<(32)
x p<(32) log log 2

p log p log3 x,

(3 2)2 log(3 2)
x log log 2

so we have (n)d3f (n) = x2


nx

1 k1 am + 2 m=1 logm x

+O

x2 . logk x

This completes the proof of Theorem 2.

92

SCIENTIA MAGNA VOL.1, NO.1

References
[1] Smarandache k-factorial at http://www. gallup. unm. edu/ smarandache/SKF.htm